Transthyretin amyloid cardiomyopathy in aortic stenosis patients scheduled for transcatheter aortic valve implantation - Margrethe Flesvig Holt; August Flø; Esra Kaya; Sophie Foss Kløve; Hege Martinsen; Kristine Amlie; Petter Storsten; Thomas Misje Mathiisen; Kristoffer Russell; Christian Hesbø Eek; Helge Skulstad; Melinda Raki; et al. (ESC Heart Failure)
Abstract Aims The prevalences of aortic stenosis (AS) and transthyretin amyloid cardiomyopathy (ATTR‐CM) increase with age. Identification of occult ATTR‐CM in patients with AS can help explain out‐of‐proportion myocardial dysfunction, aid in prognostication and prompt initiation of disease‐modifying treatment. Studies have suggested that many patients referred for transcatheter aortic valve implantation (TAVI) have concomitant ATTR‐CM, but some have included unverified ATTR‐CM in patients with ambiguous scintigrams. We aimed to assess the co‐occurrence of ATTR‐CM in patients scheduled for TAVI. Methods In patients accepted for TAVI for severe AS, we used bone scintigraphy to screen for ATTR‐CM. We defined ATTR‐CM as a cardiac tracer uptake ≥ Perugini Grade 2 in the absence of abnormal monoclonal protein or abnormal free light chain ratio. We offered bioptic verification to patients with Grade 1 or ambiguous DPD uptake. Results We included 171 consecutive patients aged 79 ± 7 years, 57% were male. Six patients (3.5%) had cardiac bone tracer uptake ≥ Perugini Grade 2 and no abnormal monoclonal protein/free light chains. Endomyocardial biopsies confirmed the diagnosis in two additional patients (1.2%), whereas five patients with low‐grade uptake did not have ATTR‐CM. In total, 8/171 patients (4.7%) were diagnosed with concomitant AS and ATTR‐CM. Most of the patients with concomitant ATTR‐CM had low‐flow low‐gradient (LFLG) AS, and 25% had a history of carpal tunnel syndrome. Conclusions We found concomitant AS and ATTR‐CM in 5% of our TAVI patients. Carpal tunnel syndrome and LFLG AS suggest concomitant ATTR.